2007
DOI: 10.1080/01443610701711706
|View full text |Cite
|
Sign up to set email alerts
|

Sex and reproduction among HIV-infected people in Maiduguri, Nigeria

Abstract: For HIV-infected people, prevention of transmission of the virus to their spouses and other sexual partners can only be achieved through abstinence and safer sex practices using condoms. New drugs and technologies are now available that can prevent vertical transmission of the virus. A total of 262 people living with HIV/AIDS (PLWHA) were interviewed to explore their sexual and reproductive desires and practices. About 75.6% of them were sexually active and 62.2% never used condoms. Although only 26.3% had no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 15 publications
2
15
1
Order By: Relevance
“…More than a quarter of a nationally representative sample of PLHIV in the USA desired to have more children, with over fifty percent of both women and men expecting to have one or more children in the future (Chen et al 2001). In a study of HIV-positive and negative African-American women in New Jersey, USA, desire for children did not vary by HIV serostatus (Wesley 2003) while in Nigeria, 71.4% of PLHIV continued to desire to have children (Chama et al 2007). …”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…More than a quarter of a nationally representative sample of PLHIV in the USA desired to have more children, with over fifty percent of both women and men expecting to have one or more children in the future (Chen et al 2001). In a study of HIV-positive and negative African-American women in New Jersey, USA, desire for children did not vary by HIV serostatus (Wesley 2003) while in Nigeria, 71.4% of PLHIV continued to desire to have children (Chama et al 2007). …”
Section: Introductionmentioning
confidence: 93%
“…Previous studies investigating fertility desires have shown that, like the general population, PLHIV desire to have children despite their HIV status (Chama et al 2007;Chen et al 2001;Nobrega et al 2007;Panozzo et al 2003;Wesley 2003). More than a quarter of a nationally representative sample of PLHIV in the USA desired to have more children, with over fifty percent of both women and men expecting to have one or more children in the future (Chen et al 2001).…”
Section: Introductionmentioning
confidence: 94%
“…PLWHA who received support from their couples had better life quality of 40.746 times than those who did not (Chama, Morrupa, & Gashau, 2007). However, Adekanle et al (2015) reported that the participants involved in the study who received continuous support from their partner were still classified as low, i.e., only 14.3 % (4 out of 28 total participants).…”
mentioning
confidence: 91%
“…As many as 48.2% PLWHA had experienced discrimination after known infected with HIV, 12.2% experienced discrimination from relatives, 12.1% from friends, 26.2% from health workers, 18.7% from their relationship and 13.2% from workplace (Adekanle, Olowookere, Adewole, Adeleke, & Ijadunola, 2015;Bouhnik, Preau, Schiltz, Obadia, & Spire, 2008;). Discrimination is one of the causes of stress and depression for PLWHA (Chama, Morrupa, & Gashau, 2007). Stress is a form of tension of physical, psychological, emotional or mental status related to a circumstance being endured while depression is an advanced stage of chronic stress which is classified as a mental disorder characterized by sad feelings, sleep disorders, appetite decreases, concentration decrease and solitude feelings (National Institute of Mental Health [NIMH], 2015).…”
mentioning
confidence: 99%
“…Data was collected using pre-tested intervieweradministered questionnaire with standard questionnaires that had been used in similar studies. 17,18 Six trained interviewers (3 in each site) who understood both languages conducted a face to face interview for data collection.…”
Section: Methodsmentioning
confidence: 99%